Modelling loan repayment behaviour and performance of smallholder farmers in badulla district - Maduwanthi, B.C.H.; Rajapaksha, K.M.D.; Thayaparan, A.; Dharmadasa, R.A.P.I.S. (University of Jaffna, 2019)
This study attempts to identify the factors that discriminate defaulters and non- defaulters and examines the factors which determine the repayment performance among the farmers in Kandaketiya division in Badulla district. The primary data was gathered through questionnaire on 110 respondents that are randomly selected from 04 villages and the data was analysed using descriptive statistics, discriminant function and Tobit model. Results of frequency showed that 89.1% of the farmers were engaged in the production of both paddy and maize while 10.9% of them were involved in paddy only. Among total farmers, 90% of them cultivated the crops in their own land and only 10% of them used in tenant land. The discriminant analysis revealed that amount of loan borrowed and farm incomes were the important discriminating variables in the study. Out of 110 farmers, 54.5% of them belonged to defaulters while 45.5% of them belonged to non- defaulters and results of the classification scores showed that, among the defaulters 71.7% of them identified correctly while among the non-defaulters 80% of them identified correctly. Tobit model results described that gender, family size, earnings from farming, types of cultivated land and amount of loan received negatively and significantly influenced the loan repayment while off- farm income positively effect on the loan repayment performance of small holder farmers in the study area. The findings of the study may guide to microfinance institutions and policy makers to take effective efforts to minimize the loan defaults among smallholder farmers in future.
Keywords: Small- holder farmers; Repayment performance; Defaulters and non- defaulters; Discriminant analysis; Tobit model